Pengaruh Kompetensi dan Persepsi Mahasiswa Terhadap Fresh Graduate Syndrom Untuk Bekerja di Perbankan Syariah - Fitria, Nita; Lestari, Widia; Shabri, Husni; Fahlefi, Rizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research aims to determine the influence of competence and perception on fresh graduate syndrome working in sharia banking for students of the Sharia Banking Study Program at UIN Mahmud Yunus Batusangkar. The type of research used is quantitative research with data collection techniques using questionnaires. The results of this research show that the competency of sharia banking alumni influences fresh graduate syndrome working in sharia banking. Students need to develop various relevant competencies during the study period to minimize the impact of the syndrome of working in sharia banking. Competencies that new graduates must have include mastery of sharia banking knowledge, technical banking skills, financial analysis skills. Apart from increasing competence, forming a positive perception of the sharia banking industry also plays an important role in preparing students to face the world of work. Simultaneously, the competence and perception of Islamic banking alumni at the State Islamic University Mahmud Yunus Batusangkar influence the fresh graduate syndrome working in sharia banking. By combining competency development and forming positive perceptions, students will be ready to face the challenges of the world of work and can reduce the risk of fresh graduate syndrome and increase opportunities for career success in the sharia banking industry.